1997
DOI: 10.1139/g97-064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among a complex of cereal cyst nematodes inferred from RFLP analysis of the ribosomal internal transcribed spacer region

Abstract: This study examined the restriction polymorphism (RFLP) of the nuclear ribosomal DNA in Heterodera avenae, H. filipjevi, H. mani, H. latipons, and the taxonomically unclear Gotland strain in order to establish a molecular characterization and phylogenetic relationships in the complex of cereal cyst nematodes (CCN). The internal transcribed spacer (ITS) and 5.8S rDNA were amplified by PCR from a single female or a cyst of 27 different geographic isolates of the CCN complex and one population of H. schachtii, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
2
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 13 publications
6
35
2
1
Order By: Relevance
“…In this study, intraspecific polymorphism based on sequence analysis was shown among populations of H. avenae, as in previous studies (Bekal et al, 1997;Subbotin et al, 1999;Handoo, 2002;Rivoal et al, 2003). The H. avenae populations in this study consisted of 2 subgroups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, intraspecific polymorphism based on sequence analysis was shown among populations of H. avenae, as in previous studies (Bekal et al, 1997;Subbotin et al, 1999;Handoo, 2002;Rivoal et al, 2003). The H. avenae populations in this study consisted of 2 subgroups.…”
Section: Discussionsupporting
confidence: 87%
“…The results of our study did not show any intraspecific polymorphism between H. filipjevi populations. Furthermore, Bekal et al (1997) did not detect any genetic variation among the different populations of this species. The H. latipons populations in this study consisted of 2 subgroups.…”
Section: Discussionmentioning
confidence: 68%
“…All three economically important species were found in Bulgaria but the latest record concerns H. filipjevi (Bekal et al, 1997). In further studies the species appeared to be much more common in cereal productive areas of the country than H. avenae and H. latipons -it was foundin 21 localities (regions of Vidin, Pleven, Velico Tarnovo, Shumen, Varna, Burgas, Sliven, Haskovo, Stara Zagora, Plovdiv and Pazardjik) of all 31 where cereal cysts nematodes were found (Ilieva and Iliev, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A propos des travaux effectués sur l'analyse de l'ADN, les techniques moléculaires ont montré une variabilité génétique au sein des populations d'Heterodera avenae [31,14] ; [32][33][34]. En Egypte [35] a étudié l'effet des amendements organiques sur la dynamique de population de H. zeae.…”
unclassified